2011
DOI: 10.1037/a0022197
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in emotional risk for self- and other-directed violence among externalizing adults.

Abstract: OBJECTIVE Women and men generally differ in how frequently they engage in other-and self-directed physical violence and may show distinct emotional risk factors for engagement in these high-impact behaviors. To inform this area, we investigated gender differences in the relationship of emotional tendencies (i.e., anger, hostility, and anhedonic depression) that may represent risk for other-directed (i.e., physical fighting, attacking others unprovoked) and self-directed violence (i.e., self-injury, suicide att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 83 publications
4
64
2
2
Order By: Relevance
“…[32][33][34] Suicidal behavior and interpersonal violence share several common risk factors, and there is evidence that troubled individuals tend to specialize in either inward-or outward-directed violence. [35][36][37] This study may be capturing differences in patterns of this expression across communities.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Suicidal behavior and interpersonal violence share several common risk factors, and there is evidence that troubled individuals tend to specialize in either inward-or outward-directed violence. [35][36][37] This study may be capturing differences in patterns of this expression across communities.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Sadeh et al (2011), Fischer & Evers (2011 found that females expressed subjective anger, or self-anger, more often than males. Buntaine and Costenbader (1997) found that both genders' self-reports (assessments) indicated no significant differences.…”
mentioning
confidence: 66%
“…Although research depicts females as more emotionally expressive, males have a reputation of being more predisposed to anger. According to Sadeh, Javdani, Finy, and Verona (2011), females experience anger, but may express it differently than males. For example, instead of expressing anger by striking objects, adolescent females may talk to friends or peers (Fischer & Evers, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gender, for example, appears to be differentially associated with violence and self-injury. Specifically, previous studies have found that males had higher interpersonal violence scores whereas females achieved higher self-directed violence scores (Sadeh et al, 2011). In addition, specific aspects of emotional disorders such as depression appear to differentiate between self-and other directed violence.…”
Section: Introductionmentioning
confidence: 90%